Algopopulism and recursive conduct: grappling with fascism and the new populisms vis-à-vis Arendt, Deleuze and Guattari, and Stiegler - Gray, Chantelle (Acta academica (Bloemfontein, South Africa), 2022)
The continuing rise of right-wing populisms and fascism across the globe, mobilised by various factors such as the use of social technologies and the weaponisation of nationalism, xenophobia, sexism and racism – to name a few – provokes important questions in terms of resistance. Moreover, given that the lines between the new populisms and fascism are becoming increasingly nebulous, it is imperative that we at least attempt to better understand the conditions – including the more hauntological, which is to say historically and structurally invisibilised – from which algorithmic governmentality and its corollary, recursive conduct, are born. On that account, I unpack two understandings of fascism, first tracing it macropolitically through the work of Hannah Arendt and, thereafter, looking at its more micropolitical and libidinal aspects vis-à-vis the work of Deleuze and Guattari. I do so because it is my contention that there is a historical correlation between Arendt’s theorisation of a generalised espionage and our contemporary surveillance systems, as well as between Deleuze and Guattari’s theorisation of desire and the harnessing of affect through machine learning methods and their deployment via social media platforms, all of which aid the propagation of certain forms of populism – and even fascism. This is what I call algopopulism: algorithmically aided politics that transforms the ‘we’ into the ‘they’ through what can be thought of as recursive conduct or the digital exercise of power and its structuring of the field of possible action and thought. In turn, I link this to Stiegler’s understanding of negative sublimation, a paralysis of the human spirit which occurs due to, among other things, the generalised proletarianisation of knowledge, ultimately provoking the short-circuiting of processes of transindividuation. Finally, I offer some notes on resistance.